Insight into the bonding mechanism in Cu/Al/Cu clad sheets via introduction of thin SUS304 interlayer - Jing Li; Haitao Gao; Charlie Kong; Hailiang Yu (Journal of Materials Research and Technology, 2022)
High bonding strength Cu/Al/Cu clad sheets with a thin stainless steel 304 (SUS304) interlayer were fabricated by rolling bonding. The bonding processes varied with different rolling reductions were investigated. The results showed that the introduction of SUS304 interlayer changed the peeling strength curves from a wave-like shape to peak-valley shape. At 70% rolling reduction, the peeling strength (peak value) of the Cu/Al/Cu clad sheets with SUS304 interlayer reached 15.5 N/mm, which was more than 5 times of those without SUS304 interlayer. The mechanism that the thin SUS304 interlayer improved the bonding strength of Cu/Al/Cu clad sheets mainly included three parts: 1) The SUS304 interlayer prohibited the formation of Cu/Al intermetallic compounds in the interface without sacrificing the elements diffusion; 2) The thin SUS304 interlayer was broken into small fragments and distributed in the interface, improving the mechanical joggle; 3) The SUS304 interlayer induced strain hardening layers by shear deformation and significantly elongated their deformation path, thus improving the bonding effect of matrix metals.